2011
DOI: 10.1143/jjap.50.116501
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation Method for Plasma-Induced Damage Profile in SiO2 Etching

Abstract: We developed a numerical simulation method for the depth profiles of plasma-induced physical damage to SiO2 and Si layers during fluorocarbon plasma etching. In the proposed method, the surface layer is assumed to consist of two layers: a C–F polymer layer and a reactive layer. Physical and chemical reactions in the reactive layer divided into several thin slabs and in the deposited C–F polymer layer, which depend on etching parameters, such as etching time, gas flow rate, gas pressure, and ion energy (V … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 28 publications
4
28
0
Order By: Relevance
“…On the other hand, this was not observed in the case of high flow rate owing to the thick polymer layer (4 nm) at the hole bottom in which the ion energy was largely reduced. It was also previously reported that the time evolution of the damage distribution during SiO 2 =Si multilayer etching is predicted well, and that even in the case of high selectivity (∼20), considerable Si damage can be observed just before overetching occurs because of the thin polymer and SiO 2 layers 69,114) used, as shown in Fig. 20, and this agrees with the results of MD calculations.…”
Section: Surface Reactionsupporting
confidence: 89%
See 3 more Smart Citations
“…On the other hand, this was not observed in the case of high flow rate owing to the thick polymer layer (4 nm) at the hole bottom in which the ion energy was largely reduced. It was also previously reported that the time evolution of the damage distribution during SiO 2 =Si multilayer etching is predicted well, and that even in the case of high selectivity (∼20), considerable Si damage can be observed just before overetching occurs because of the thin polymer and SiO 2 layers 69,114) used, as shown in Fig. 20, and this agrees with the results of MD calculations.…”
Section: Surface Reactionsupporting
confidence: 89%
“…16. By using a voxel model 113) connected to the slab model, 114) which is then called the voxel-slab model, a simulation technology for the SiN SW etching process with new concepts for gas transportation, detailed surface reactions that are dependent on the H=N ratio, and etch front evolution has recently been reported; 115) this technology can calculate the etched profile and damage distribution simultaneously in a 3D space with a short calculation run time. Figure 17 shows a schematic image of the calculation flow of the 3D voxelslab model described above.…”
Section: Variations In Etched Surface Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…4 nm) measured as a function of oxygen flow rate are shown in Figure 4a for the ICP system and b for the CCP system. In general, during the etching of SiO 2 by fluorocarbon plasmas, F radicals react with Si on the SiO 2 surface and are removed from the surface as SiF x while C radicals react with O on the SiO 2 surface and are removed from the surface as CO x [20]. As shown in Figure 4a,b, the increase in densities of radicals such as CF 2 , CO, C 2 , and F with increasing oxygen flow rate could be observed in both the ICP system and the CCP system due to the increased dissociation of fluorocarbon by oxygen radicals in the plasmas.…”
Section: Resultsmentioning
confidence: 99%